2007
DOI: 10.1590/s1516-14392007000200015
|View full text |Cite
|
Sign up to set email alerts
|

Surface area, crystal morphology and characterization of transition alumina powders from a new gibbsite precursor

Abstract: A new procedure was used to prepare a microcrystalline powder constituted by thin euhedral hexagonal gibbsite plates, 0.2 to 0.6 µm in diameter and 32 nm thick. The powder, fired between 200 and 1000 °C, produced chi and kappa transition aluminas. Alpha-alumina is formed from 1000 °C and recrystallized up to 1500 °C. At 1000 °C, kappa-and alpha-alumina coexisted, but kappa-alumina could only be characterized by SAED. The details of the internal organization of the transition alumina pseudomorphs were clearly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Li et al [32] revealed that the crystal growth of bayerite and gibbsite follows different pathways and, as can be seen in the results of the present report, the crystal growth of the bayerite and gibbsite were strongly influenced by the precipitation pH. Next, the XRD pattern of the aluminum oxide obtained by thermal treatment of Gel 8-80 at 500 • C is attributed to the formation of poorly crystalline chi-alumina, and is very similar to that found by Meephoka et al [33], Mekasuwandumrong et al [34], Vieira-Coelho et al [35] and Tsuchida and Ichikawa [36], with characteristic broad peaks located at 37 • , 40 • , 46 • , 60 • and 67 • . As in the present report, the chi-alumina was obtained by the cited authors from pure gibbsite.…”
Section: Resultssupporting
confidence: 91%
“…Li et al [32] revealed that the crystal growth of bayerite and gibbsite follows different pathways and, as can be seen in the results of the present report, the crystal growth of the bayerite and gibbsite were strongly influenced by the precipitation pH. Next, the XRD pattern of the aluminum oxide obtained by thermal treatment of Gel 8-80 at 500 • C is attributed to the formation of poorly crystalline chi-alumina, and is very similar to that found by Meephoka et al [33], Mekasuwandumrong et al [34], Vieira-Coelho et al [35] and Tsuchida and Ichikawa [36], with characteristic broad peaks located at 37 • , 40 • , 46 • , 60 • and 67 • . As in the present report, the chi-alumina was obtained by the cited authors from pure gibbsite.…”
Section: Resultssupporting
confidence: 91%
“…Also high resolution TEM analysis supports a hexagonal arrangement. 100 However, all authors agree the oxygen sublattice is best described as a dense packing of oxygen planes with either a fully random stacking sequence one that is ordered only locally. Therein, tetrahedral and octahedral Al sites are both considered to be disordered, and typically in a ratio of roughly 0.3.…”
Section: Gibbsite → χ → κ → α-Aluminamentioning
confidence: 99%
“…It is characterized with good thermal and chemical stability [ 9 ]. Its texture is defined with a high specific surface area (135–190 m 2 /g) [ 10 , 11 ], appropriate pore size distribution, pore size and surface acidity (derived from the local microstructure, phase composition, chemical composition). Moreover, the presence of acid/base centers may offer an additional source of active centers for catalysts [ 12 ].…”
Section: Introductionmentioning
confidence: 99%